Trends in the Introduction of Modern Information and Communication Technologies in Educational Practice (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
The rapid integration of modern information and communication technologies (ICT) into educational systems marks a significant shift in teaching and learning paradigms across the globe. This paper analyzes critical documents such as the outcomes of the World Summit on the Information Society, the Eurydice network’s studies on ICT usage in European schools, and recommendations by the European Parliament and Council on key competences for lifelong learning, among other publications. It explores the experience of leading countries in implementing ICT in education. These include adopting ICT competencies as a means to acquire other essential skills, the introduction and funding of national informatics education programs, and the proliferation of cloud technologies, e-learning, and distance education. The development of repositories for electronic resources and the creation of models for assessing the state of informatics in educational institutions are also discussed. Key trends in the development of information technologies in education are highlighted, revealing a strategic emphasis on enhancing accessibility, interactive learning environments, and the continuous adaptation of educational frameworks to accommodate new technological potentials. This examination not only underscores the transformative impacts of ICT on educational methods but also the critical need for ongoing research to optimize and tailor these technologies to diverse learning landscapes.